On the physicians who deserved «practical official distinctions» - V. P. Nikolaev (Бюллетень сибирской медицины, 2005)
Historical data on the physicians who deserved love and respect of local population by selfless performing medical debt and serving to goods in boundless open spaces of the Yakutia in XVIII – the beginning of XX centuries are presented in the paper.